Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.compstruct.2018.03.050
|View full text |Cite
|
Sign up to set email alerts
|

In-plane crashworthiness of bio-inspired hierarchical honeycombs

Abstract: Biological tissues like bone, wood, and sponge possess hierarchical cellular topologies, which are lightweight and feature an excellent energy absorption capability. Here we present a system of bio-inspired hierarchical honeycomb structures based on hexagonal, Kagome, and triangular tessellations. The hierarchical designs and a reference regular honeycomb configuration are subjected to simulated in-plane impact using the nonlinear finite element code LS-DYNA. The numerical simulation results show that the tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(35 citation statements)
references
References 30 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…Yin et al [30] compared three different hierarchical honeycombs, and confirmed that the triangular hierarchical honeycomb has the best crushing performance compared to other two hierarchical honeycombs. Xu et al [31] used the self-similar hierarchical hexagonal columns to improve crashworthiness performance of vehicles.…”
Section: Introductionmentioning
confidence: 98%
“…Yin et al [30] compared three different hierarchical honeycombs, and confirmed that the triangular hierarchical honeycomb has the best crushing performance compared to other two hierarchical honeycombs. Xu et al [31] used the self-similar hierarchical hexagonal columns to improve crashworthiness performance of vehicles.…”
Section: Introductionmentioning
confidence: 98%
“…e comparison of the dynamic crushing mode in Ref. [12] and its simulation was performed, which could be seen in Figure 3. From their comparison, it can be known that the crushing mode and its collapse condition of honeycombs meet with that of existing test specimens well.…”
Section: Validation Of Modelmentioning
confidence: 99%
“…Meanwhile, the nominal plateau stress of honeycomb materials in the same loading conditions reduces as the missing cells increase. According to the axial compressive test, Barnes et al [10] and Chung and Waas [11] investigated the influence of cell configuration on crushing modes of opencell foam metal as well as circular cell polycarbonate honeycombs, respectively, which revealed the mechanism of crushing modes and mechanical behaviors for various honeycomb materials with diverse cell configurations [12] as well as varied loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical and analytical studies indicate that the introduction of structural hierarchy in regular honeycombs results in improved heat resistance and thermal anisotropy. Then, Yin et al [22] studied the in-plane crashworthiness of the hierarchical honeycomb group above, using the nonlinear finite element code LS-DYNA. The numerical simulation results indicate that the triangular hierarchical honeycomb provides the best performance compared to the other two hierarchical honeycombs and features more than twice the energy absorbed by the regular honeycomb under similar loading conditions.…”
Section: Introductionmentioning
confidence: 99%